A Study on Student Satisfaction with E-learning Platforms Among the KJC Student - Ringzuala, Joshua V. L.; Thomas, Cherian (International Journal of Research in Interdisciplinary Studies, 2025)
EINVALING and KJC Easton (Kristu Jayanti College) investigated the impact of the course on student satisfaction with e-learning systems by students taking KJC. The research aimed to determine the relationship between various factors like usability, quality of content, user accessibility, engagement level, and technical support. A questionnaire gave relative quantitative information from student departments. Findings concurred with the reality that as useful as it is to possess the locking feature of an e-learning platform, it does create issues such as poor technical support or the lack of interaction tools, which contribute to lower satisfaction. The research offers important insights that can be beneficial for students to achieve higher engagement and perform better on such e-learning platforms. Students of KJC were the object of observation for such impressions.